Modulation of cytokines production by indomethacin acute dose during the evolution of ehrlich ascites tumor in mice - Gentile, Luciana Boffoni [UNESP]; Queiroz-Hazarbassanov, Nicolle; Massoco, Cristina de Oliveira; Fecchio, Denise [UNESP] (Hindawi Publishing Corporation, 2015)
The aim of the present study was to investigate the influence of a nonselective COX1/COX2 inhibitor (indomethacin) on tumor growth of Ehrlich Ascites Tumor (EAT) in mice, using as parameters the tumor growth and cytokine profile. Mice were inoculated with EAT cells and treated with indomethacin. After 1, 3, 6, 10, and 13 days the animals were evaluated for the secretion of TNFα, IL-1α, IL-2, IL-4, IL-6, IL-10, and IL-13 and PGE2 level in peritoneal cavity. The results have shown that EAT induces PGE2 production and increases tumor cells number from the 10th day. The cytokine profile showed EAT induces production of IL-6 from 10th day and of IL-2 on 13th day; the other studied cytokines were not affected in a significant way. The indomethacin treatment of EAT-bearing mice inhibited the tumor growth and PGE2 synthesis from the 10th day. In addition, the treatment of EAT-bearing mice with indomethacin has stimulated the IL-13 production and has significantly inhibited IL-6 in the 13th day of tumor growth. Taken together, the results have demonstrated that EAT growth is modulated by PGE2 and the inhibition of the tumor growth could be partly related to suppression of IL-6 and induction of IL-13.